Effects of water and food deprivation on lactating Nubian goats - Ali, K.E.; Mirghani, T. (1983)
Investigations were carried out on the effects of water and food deprivation on the milk yield, body weight, blood composition and urine volume of lactating Nubian goats. The animals survived 4 days of deprivation of either food or both food and water, but these treatments resulted in about 10 per cent loss in body weight, 85 per cent drop in urine volume, and cessation of milk production, but no significant changes in packed cell volume, serum sodium, potassium and total protein. The change in body weight could be reversed within 1 day, but the initial milk yield was not resumed during the 2 weeks immediately following restoration of food and water.